EFEKTIVITAS DAN EFISIENSI MESIN-MESIN DALAM SATU RANGKAIAN PADA PROSES PRODUKSI KAYU LAPIS (STUDI KASUS DI PT SURYA SATRYA TIMUR) - Gottrezeki Xaverius Nadeak; Gusti Abdul Rahmat Thamrin; Adi Rahmadi (Universitas Lambung Mangkurat, 2021)
This research aims to analyze the effectiveness and efficiency value of plywood production machines. This research was conducted by observing and recording the production flow or workflow of the machines in a series on the plywood production process used in PT Surya Satrya Timur. Data retrieval is only taken on the morning shift which is from 07.00 to 17.00 WITA and on each machine is observed three times. Based on the data obtained for log cutting machine, effectiveness (90%) and efficiency (41.70%). Rotary machine, effectiveness (90%) and efficiency (81.56%). Machine Continues Dryer, effectiveness (90%) and efficiency (85.19%). Core jointer machine, effectiveness (90%) and efficiency (76.1%). Glue spreader machine, effectiveness (90%) and efficiency (59.43%). Cold press machine, effectiveness (90%) and efficiency (30.03%). Hot press machine, effectiveness (90%) and efficiency (79.27%). Sizer machine, effectiveness (83.34%) and efficiency (37.41%). Sander machine, effectiveness (90%) and efficiency (54.15%). Thus, the effectiveness value of the use of machines in one series at PT Surya Satrya Timur has achieved a high effectiveness value of 90% on eight machines in the phase of the plywood production process including Log cutting, Rotary, Continues Dryer, Core Jointer, Glue Spreader, Cold Press, Hot press and Sander and one machine the value is not yet high i.e. at the stage Sizer only reached 83.34%. While the efficiency value of the machine at PT Surya Satrya Timur ranges from 30.03% - 85.19%. The most efficient stage in the production process is the Continues Dryer stage of 85.19% and the lowest efficiency is at the Cold Press, Sizer and Log Cutting stages of 30.03%, 37.41 and 41.70% respectivelyPenelitian ini bertujuan untuk menganalisis nilai efektifitas dan efisiensi mesin-mesin produksi kayu lapis. Penelitian ini dilakukan dengan mengamati dan mencatat alur produksi atau alur kerja mesin-mesin dalam satu rangkaian pada proses produksi kayu lapis yang digunakan di PT Surya Satrya Timur. Pengambilan data hanya diambil pada shift pagi yaitu dari jam 07.00 sampai 17.00 WITA dan pada setiap mesin dilakukan pengamatan sebanyak tiga kali. Berdasarkan data yang didapat untuk mesin Log cutting, efektivitas (90%) dan efisiensi (41,70%). Mesin Rotary, efektivitas (90%) dan efisiensi (81,56%). Mesin Continues Dryer, efektivitas (90%) dan efisiensi (85,19%). Mesin Core jointer, efektivitas (90%) dan efisiensi (76,1%). Mesin Glue spreader, efektivitas (90%) dan efisiensi (59,43%). Mesin Cold press, efektivitas (90%) dan efisiensi (30,03%). Mesin Hot press, efektivitas (90%) dan efisiensi (79,27%). Mesin Sizer, efektivitas (83,34%) dan efisiensi (37,41%). Mesin Sander, efektivitas (90%) dan efisiensi (54,15%). Jadi, Nilai efektifitas penggunaan mesin pada satu rangkaian di PT Surya Satrya Timur sudah mencapai nilai efektifitas yang tinggi sebesar 90% pada delapan mesin tahap proses produksi kayu lapis diantaranya tahap Log cutting, Rotary, Continues Dryer, Core Jointer, Glue Spreader, Cold Press, Hot press dan Sander dan satu mesin nilainya belum tinggi yaitu pada tahap Sizer hanya mencapai 83,34%. Sedangkan nilai efisiensi mesin pada PT Surya Satrya Timur berkisar antara 30,03% - 85,19%. Tahap yang paling efisien dalam proses produksi yaitu tahap Continues Dryer sebesar 85,19% dan efisiensi paling rendah yaitu pada tahap Cold Press, Sizer dan Log Cutting masing – masing 30,03%, 37,41 dan 41,70%